1991
DOI: 10.1071/sr9910619
|View full text |Cite
|
Sign up to set email alerts
|

A soil sulfur test for pastures and crops

Abstract: Soil testing for S has generally been unsuccessful when using extractants that remove only sulfate from the soil.An assessment of a range of extractants to predict S status was undertaken on soil samples taken from 18 field trials in northern N.S.W. The extractants were water, 0 . 0 1 M monocalcium phosphate (MCP) and 0 . 5 M NaHC03, 0.25 M KC1 heated for 3 h at 100, 80, 40, or 25°C. The highest correlation between soil S test level and % maximum yield was found in the 40°C KC1 extractant (r2 = 0.73). This com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
114
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(118 citation statements)
references
References 14 publications
4
114
0
Order By: Relevance
“…Laboratory analysis showed that the surface soil was loamy sand and contained 1 mg NO 3 -N and 1 mg NH 4 -N/kg (Searle 1984), 2 mg P and 15 mg K/kg (Colwell 1963), 2 mg S/kg (Blair et al 1991), and 13 g organic C/kg (Walkley and Black 1934) Basal nutrients were evenly mixed in the soil of each pot. Six seeds were sown per pot, and 10 days later the seedlings were thinned to two uniform plants.…”
Section: Crops and Growth Conditionsmentioning
confidence: 99%
“…Laboratory analysis showed that the surface soil was loamy sand and contained 1 mg NO 3 -N and 1 mg NH 4 -N/kg (Searle 1984), 2 mg P and 15 mg K/kg (Colwell 1963), 2 mg S/kg (Blair et al 1991), and 13 g organic C/kg (Walkley and Black 1934) Basal nutrients were evenly mixed in the soil of each pot. Six seeds were sown per pot, and 10 days later the seedlings were thinned to two uniform plants.…”
Section: Crops and Growth Conditionsmentioning
confidence: 99%
“…The soil P and S levels were measured using the Colwell P method (Colwell 1963) and the KCl-40 S test (Blair et al 1991).…”
Section: Soil Fertility Targetsmentioning
confidence: 99%
“…Both of these soil tests give an estimate of the level of available P and S to pasture systems and have been calibrated for the Northern Tablelands and critical concentrations determined (Holford and Crocker 1988;Blair et al 1991). The maintenance applications of farmlets B and C were set such that they were likely to still be responsive to P and S applications, while farmlet A was designed to achieve >90% of potential pasture production in the region.…”
Section: Soil Fertility Targetsmentioning
confidence: 99%
See 2 more Smart Citations